PENTINGNYA PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR ABAD 21 : KAJIAN LITERATUR - Zunika Agung Rahayu; Arri Handayani; Dini Rakhmawati (STKIP Subang, 2024)
This article aims to elaborate and reveal the importance of character education at the elementary school level in the 21st century. The main issue discussed in this article is character education as a unique national identity that is inherited and the formation of habits in the midst of 21st century digital technology. Sources This is obtained from actual data with emphasis on citing articles and journals in which they are published. The literature study in preparing this article is a literature review using a qualitative descriptive method carried out through reading, concluding and developing the data obtained as research material used. Alternative problem solving in this article focuses on the fact that character education cannot only use theory, but requires role models or examples as well as supervision.